Influência dos parâmetros de corte sobre o fresamento frontal do aço ASTM 743 CA6NM com ferramenta de metal-duro - Sponchiado, Mateus André (2019)
This study shows the influence of the cutting parameters in the face milling of ASTM 743 CA6NM martensitic stainless steel with PVD coated carbide tool. It was analyzed the effect of cutting speed (vc) and feed per tooth (fz) on tool wear and also on the surface roughness. Thus, experiments were designed and they were statistically analyzed through a factorial design. The results indicate that cutting speed (vc) and feed per tooth (fz) have significant influence on the tool wear. Furthermore, the values of the surface roughness increased when the feed per tooth (fz) was also increased. The analyses were done using the Scanning Electron Microscope (SEM), aided by the Energy Dispersive Spectrometry (EDS), and have shown us that several wear mechanisms act simultaneously with predominant influence of attrition.